2004
DOI: 10.1080/13697130400001307
|View full text |Cite
|
Sign up to set email alerts
|

Role of progestins with partial antiandrogenic effects

Abstract: An experts' meeting on the 'Role of progestins with partial antiandrogenic effects' was held in Berlin from January 19 to 22, 2001. The meeting was chaired by Dr R. Sitruk-Ware (New York, USA) and participants included Ms F. Fruzzetti (Pisa, Italy), J. Hanker (Trier, Germany), J. Huber (Vienna, Austria), F. Husmann (Bad Sassendorf, Germany), S. O. Skouby (Copenhagen, Denmark), J. H. H. Thijssen (Utrecht, The Netherlands), and R. Druckmann (Nice, France). The present paper reports the conclusions of the meeting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 72 publications
0
3
0
1
Order By: Relevance
“…observed with combination estrogen plus progestin hormone therapy (46), although some suggest that progestins with high androgenic properties may antagonize the beneficial changes in LDL and HDL induced by estrogen (39,40,46). The previous studies used oral estrogens, which could have a greater influence on lipid concentrations due to first-pass metabolism via the liver than transdermal estrogens.…”
Section: Discussionmentioning
confidence: 99%
“…observed with combination estrogen plus progestin hormone therapy (46), although some suggest that progestins with high androgenic properties may antagonize the beneficial changes in LDL and HDL induced by estrogen (39,40,46). The previous studies used oral estrogens, which could have a greater influence on lipid concentrations due to first-pass metabolism via the liver than transdermal estrogens.…”
Section: Discussionmentioning
confidence: 99%
“…However, other progestin‐only contraceptives in our study, such as the injectable contraceptive, were associated with greater blood pressure, highlighting the potentially important role of progestin type. Progestins are synthetic forms of endogenous progesterone and can be derived from either 17‐a‐hydroxyprogesterone or 19‐nortestosterone (Ghatge et al, 2005 ; Oelkers, 1996 ) resulting in wide variation in both progestational and androgenic activity (Sarna et al, 2009 ; Sitruk‐Ware, 2004 ; Sitruk‐Ware et al, 2004 ). High androgenic activity, predominately present in testosterone‐derived progestins, is associated with higher cardiovascular risk (Nath & Sitruk‐Ware, 2009 ; Sitruk‐Ware, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are majorly three types of PR LBD ligands: agonists, antagonists and SPRMs. P4 and other progestins, though have different pharmacological profiles and effects (Sitruk-Ware, 2004; Sitruk-Ware et al, 2004), they generally activate the functional gene expressions, repress estrogen induced endometrial proliferation, and inhibit the endometrial mitogenic effects of estrogens (Vegeto et al, 1993; Kraus et al, 1995; Schindler et al, 2003). Another type of PR LBD ligands, the SPRMs, such as asoprisnil (DeManno et al, 2003), would in some case bring the partial agonism as observed in clinical trials and animal tests (Elger et al, 2000; Spitz, 2003; Chwalisz et al, 2005a,b).…”
Section: Introductionmentioning
confidence: 99%